2019
DOI: 10.1042/bsr20190604
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A: a potential diagnostic biomarker and therapeutic target in human diseases

Abstract: Transcription factor B-cell lymphoma/leukemia 11A (BCL11A) gene encodes a zinc-finger protein that is predominantly expressed in brain and hematopoietic tissue. BCL11A functions mainly as a transcriptional repressor that is crucial in brain, hematopoietic system development, as well as fetal-to-adult hemoglobin switching. The expression of this gene is regulated by microRNAs, transcription factors and genetic variations. A number of studies have recently shown that BCL11A is involved in β-hemoglobinopathies, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 105 publications
(137 reference statements)
0
51
0
Order By: Relevance
“…The deletion of CDKN2A has been associated with poor survival of affected glioma patients [ 53 , 54 ]. BCL11A is mainly known as a transcriptional repressor important for brain development [ 55 ]. COL1A1 has been shown to be involved in cell invasion [ 56 ], and MET is an important factor involved in a variety of processes that contribute to the malignancy of gliomas [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of CDKN2A has been associated with poor survival of affected glioma patients [ 53 , 54 ]. BCL11A is mainly known as a transcriptional repressor important for brain development [ 55 ]. COL1A1 has been shown to be involved in cell invasion [ 56 ], and MET is an important factor involved in a variety of processes that contribute to the malignancy of gliomas [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we determined that 4 out of 5 of these genes ( GAB1 , CIITA, HLA-DQA1, HLA-DQB1) are predicted to be gene targets of the BCL11A transcription factor. BCL11A is a zinc finger protein that is expressed in hematopoietic cells and in the brain and whose presence is linked to hematological malignancies 41, 70 . This TF has been shown to play an important role in lymphoid development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BCL11A is highly expressed in some haematological malignancies and malignant solid tumours and is associated with poor clinical prognosis 1 .We have previously shown that BCL11A is a triple negative breast cancer (TNBC) gene 12 . BCL11A is overexpressed in TNBC including basal-like breast cancer (BLBC), and its genomic locus is amplified in up to 38% of BLBC.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor B-cell lymphoma/leukaemia 11A (BCL11A) is a zinc finger protein mainly expressed in the brain and hematopoietic cell lineages 1,2 . BCL11A is part of the ATP-dependent chromatin remodelling mammalian SWI/SNF complex 3 , which enables nucleosome restructuring, ensuring DNA is accessible for transcription replication and DNA repair 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation